Case report: Kikuchi-Fujimoto disease presenting with persistent fever and widespread lymphadenopathy in a young adult - Ye, Jing; Yu, Qian; Chen, Yan; Huang, Chunping (Frontiers in Immunology, 2025)
Kikuchi-Fujimoto disease (KFD) is a rare, self-limiting condition typically characterized by fever and lymphadenopathy. The exact etiology remains unclear but is suspected to be associated with viral infections and autoimmune responses. This report presents the case of a 32-year-old Chinese male who was admitted with recurrent high fever, lymphadenopathy, and hepatosplenomegaly. Initial treatment was ineffective, and a lymph node biopsy subsequently confirmed the diagnosis of KFD, with evidence of cytomegalovirus infection. Following treatment with corticosteroids, the patient’s symptoms improved rapidly, and no relapse was observed during follow-up after discharge. This case highlights the diagnostic challenges of KFD, particularly in distinguishing it from lymphoma and systemic lupus erythematosus. Accurate and timely diagnosis is crucial to avoid unnecessary treatments, and long-term follow-up is recommended to monitor for potential disease progression.